Listeriosis Outbreak in Sheep Raised in Feedlots in the Southern Region of Rio Grande do Sul State, Brazil - Ribeiro, Luiza Soares; Scheid, Haide Valeska; Marques, Lucas dos Santos; Venancio, Fabiano da Rosa; da Silva, Elisa Rocha; Ladeira, Silvia Regina; Schild, Ana Lucia (Acta Scientiae Veterinariae, 2022)
Background: A listeriosis outbreak in a sheep fattening feedlot in the Southern Region of Rio Grande do Sul State, Brazil is described. This disease is caused by Listeria monocytogenes and represents a risk to public health since it affects not only ruminants but also humans. This agent is widely spread in the environment, such as in the soil and water. It is also found in decaying vegetable matter and the feces and fluids of domestic animals. The aim of this study was to describe a listeriosis outbreak in sheep raised in feedlots, its epidemiology, and to establish the importance of this disease in this type of sheep management system, evaluate the possible sources of infection, and suggest ways to control it. Cases: Sheep were kept in a 2-sector shed, one with east solar orientation and the other with west solar orientation, the latter with free access to domestic birds. Sheep were fed silage and concentrate. Seven sheep were affected, 5 died and 2 recovered. Clinically, the sheep displayed loss of balance, excessive drooling, and tremors; one exhibited circling, head deviation, apathy, nystagmus, lateral recumbency, paddling, and labored breathing. At necropsy, macroscopic lesions were not found, and histologically several micro-abscesses and perivascular cuffs with lymphocytes, macrophages, and neutrophils were present in the brain stem. Listeria monocytogenes suspected colonies were observed in the microbiological culture, and the bacteria was identified by biochemical analysis. The immunohistochemistry test in brain stem sections was positive for the antibody BD DifcoTM Listeria O Antiserum Poly Serotypes 1 and 4. Discussion: A listeriosis outbreak in a feedlot sheep was confirmed through epidemiological findings, histological lesions, bacterial culture, and immunohistochemistry analysis. This infection is frequent in sheep fed silage of poor quality or other food with improper storage and lack of hygiene. In the present outbreak, the bacteria were isolated from silage. However, it is likely that domestic birds, which were raised in the same place and had free access to the west sector of the feedlot, were the initial source of infection, because the sheep from the opposite sector (east) did not get ill. The disease caused by environmental contamination or through contact with fluids and feces of ducks, chickens, cattle, and pigs has already been described in outbreaks that occurred in the central region of Rio Grande do Sul. Sheep aggregation in feedlot systems is also a favorable factor for the development of the bacteria and the occurrence of outbreaks because the accumulation of feces and urine cause humidity on the stalls. This allows outbreaks to occur in other seasons of the year, such as in the outbreak reported herein. The exchange of silage that served as food for sheep was another control measure, and new cases were not reported 8 months after these procedures were taken. In the outbreak studied, 2 sheep that exhibited clinical signs were treated with oxytetracycline and recovered. Some authors report that treatment for listeriosis is inefficient because neurological lesions are irreversible. Nonetheless, other studies have reported the recovery of some animals when they were treated with oxytetracycline or a combination of oxytetracycline and dexamethasone or ampicillin and gentamicin like in the outbreak described in this paper. Keywords: Listeria monocytogenes, central nervous system, silage, feedlot, ovine.